Caregiver's readiness for change as a predictor of outcome and attendance in an intervention programme for children and adolescents with obesity: a secondary data analysis. Issue 3 (27th March 2019) - Anderson, Yvonne C; Dolan, Gerard M S; Wynter, Lisa E; Treves, Katharine F; Wouldes, Trecia A; Grant, Cameron C; Cave, Tami L; Smiley, Anna J; Derraik, José G B; Cutfield, Wayne S; Hofman, Paul L
Abstract : Objective/design: It remains unclear as to the efficacy of readiness for change measurements in child and adolescent obesity intervention programmes. This observational study aimed to determine whether the caregiver's stage of change could predict outcome and adherence to treatment in an intensive intervention programme for children and adolescents with obesity. Setting: Participants were from the Whānau Pakari randomised clinical trial, a community based multi-disciplinary intervention programme for obesity in Taranaki, New Zealand. Participants: Eligible participants (recruited January 2012 to August 2014) were aged 5–16 years and had a body mass index (BMI) ≥98th centile or BMI >91st centile with weight-related comorbidities. Interventions: This study only assessed participants randomised to the high-intensity intervention programme (6-month assessments with weekly group sessions for 12 months) given attendance data were required (n=96). Primary and secondary outcome measures: Primary trial outcome was BMI SD score (SDS). Secondary outcome measures included indices such as fruit and vegetable intake, 550-m run/walk time and quality of life scores. At baseline assessment, participants (if >11 years old) and their accompanying adult were assessed for readiness to make healthy lifestyle change. Results: A quantitative measure of stage of change in caregivers was not a predictor of primary or secondary outcomes (change in BMI SDS pre-contemplation/contemplation −0.08, 95% CI −0.18 to 0.03, action −0.16, 95% CI −0.27 to –0.05, p=0.27), or overall attendance in the weekly activity sessions (40.0% vs 37.1%, respectively, p=0.54) in the child or adolescent. Conclusions: Caregiver's stage of change was not a predictor of success in this multi-disciplinary assessment and intervention programme for children and adolescents with obesity. Future research needs to determine participants' factors for success. Trial registration number: ANZCTR12611000862943; Post-results.